PROMOSI PARIWISATA DALAM KONTEN INSTAGRAM @DISPAREKRAFDKI SEBAGAI STRATEGI DIGITAL TOURISM MENARIK WISATAWAN - Bawa Mulyono Hadi (JURNAL ILMIAH EDUNOMIKA, 2024)
Promotion of the tourism sector has an important role in supporting the Indonesian economy. Tourism marketing in the digital era encourages tourism resources to make optimal use of technology. This study aims to (1) find out the digital tourism strategy used by DKI Jakarta Disparekraf in Instagram content @disparekrafdki; (2) find out the effectiveness of the digital tourism strategy by the DKI Disparekraf in promoting DKI Jakarta tourism through Instagram content. This research is a descriptive qualitative research. The results of this study indicate that (1) the digital tourism strategy used by the DKI Jakarta Tourism and Creative Economy Department in promoting tourist destinations in DKI Jakarta through the Instagram platform contains dimensions of entertainment, interaction, trends and customization; (2) Promotion of the tourism sector by utilizing digital tourism strategies through the Instagram platform which tends to be simple, global and interactive is an effective and inexpensive way.